Microsoft SharePoint technologies planning, design, and implementation - Laahs, Kevin; McKenna, Emer.; Vanamo, Veli-Matti. (Amsterdam ; Boston : Elsevier/Digital Press : HP Invent, 2005)
Microsoft SharePoint Technologies: Planning, Design and Implementation provides an in-depth examination of the tasks involved in planning, designing and deploying SharePoint in your enterprise. The book examines SharePoint from the user's perspective, the administrator's perspective, and the application developer's perspective and looks at how you can maximize your investment by integrating SharePoint features with Office 2003 and other enterprise applications in your environment. The authors are experienced consultants that have helped many large corporations deploy Microsoft technologies within their enterprise. This book is filled with practical experience and knowledge gained from working with customers in the field. * Complete guide to getting the most out of your SharePoint deployments * Critical techniques for system architects to design and deploy SharePoint Technologies * Features most important issues for day to day efficient management and usage * How to customize and extend your SharePoint environment for your own needs.
How did we get here? -- Windows SharePoint services -- "Office" integration -- SharePoint portal server -- People and personalization -- Search -- SharePoint products and technologies architecture -- Planning SharePoint features -- Planning the deployment architecture -- Deploying sharepoint technologies -- Migrating data to SharePoint products and technologies -- Supporting and managing a SharePoint deployment -- Introduction to SharePoint development -- Web Part development -- Deploying and debugging Web parts -- Customizing SharePoint using FrontPage 2003 -- Customizing and extending SharePoint.
"Communications"--Cover.
Includes index.
Keywords: Intranets (Computer networks); Web servers; Electronic books